Compared Heritability of Chronotype Instruments in a Single Population Sample. Issue 5 (October 2021) - Leocadio-Miguel, Mario A.; Ruiz, Francieli S.; Ahmed, Sabrina S.; Taporoski, Tâmara P.; Horimoto, Andréa R. V. R.; Beijamini, Felipe; Pedrazzoli, Mario; Knutson, Kristen L.; Pereira, Alexandre C.; von Schantz, Malcolm
It is well established that the oldest chronotype questionnaire, the morningness-eveningness questionnaire (MEQ), has significant heritability, and several associations have been reported between MEQ score and polymorphisms in candidate clock genes, a number of them reproducibly across populations. By contrast, there are no reports of heritability and genetic associations for the Munich chronotype questionnaire (MCTQ). Recent genome-wide association studies (GWAS) from large cohorts have reported multiple associations with chronotype as assessed by a single self-evaluation question. We have taken advantage of the availability of data from all these instruments from a single sample of 597 participants from the Brazilian Baependi Heart Study. The family-based design of the cohort allowed us to calculate the heritability (h 2 ) for these measures. Heritability values for the best-fitted models were 0.37 for MEQ, 0.32 for MCTQ, and 0.28 for single-question chronotype (MEQ Question 19). We also calculated the heritability for the two major factors recently derived from MEQ, "Dissipation of sleep pressure" (0.32) and "Build-up of sleep pressure" (0.28). This first heritability comparison of the major chronotype instruments in current use provides the first quantification of the genetic component of MCTQ score, supporting its future use in genetic analysis. Our findings also suggest that the single chronotype question that has been used for large GWAS analyses captures a larger proportion of the dimensions of chronotype than previously thought.